2022
DOI: 10.1111/aos.15090
|View full text |Cite
|
Sign up to set email alerts
|

Association of the prolonged use of anti‐glaucoma medications with the surgical failure of ab interno microhook trabeculotomy

Abstract: Purpose: This study examined the perioperative factors affecting surgical success in ab interno microhook trabeculotomy (lTLO). Methods: A total of 146 consecutive patients who underwent lTLO were included in this retrospective study. We performed Cox proportional hazard modelling by setting surgical success at 1 year as an objective variable. The explanatory variables included age, sex, glaucoma type, preoperative intraocular pressure (IOP), glaucoma drug score, mean deviation (MD) of the Humphrey visual fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 38 publications
1
31
2
Order By: Relevance
“…Mori et al compared the effectiveness and safety of µLOT for all types of glaucoma between 1-quadrant and 2-quadrant incision groups and concluded that the 1-year success rate was not significantly different, but 2-quadrant incision groups showed a significantly higher rate of transient IOP rise post-operatively [24]. Further, the relationship between the prolonged use of anti-glaucoma medications and surgical outcomes should be investigated in the future because Okuda et al recently reported that the prolonged use of anti-glaucoma drugs was significantly associated with surgical failure after µLOT for all types of glaucoma [25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mori et al compared the effectiveness and safety of µLOT for all types of glaucoma between 1-quadrant and 2-quadrant incision groups and concluded that the 1-year success rate was not significantly different, but 2-quadrant incision groups showed a significantly higher rate of transient IOP rise post-operatively [24]. Further, the relationship between the prolonged use of anti-glaucoma medications and surgical outcomes should be investigated in the future because Okuda et al recently reported that the prolonged use of anti-glaucoma drugs was significantly associated with surgical failure after µLOT for all types of glaucoma [25].…”
Section: Discussionmentioning
confidence: 99%
“…µLOT was performed according to an original procedure devised by Tanito et al [21] with a minor modification as previously described [24,25]. In brief, for eyes undergoing 1quadrant µLOT, after a corneal paracentesis was created, the aqueous humor was replaced by cohesive viscoelastic.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…A long-term history of topical glaucoma medication use and high preoperative glaucoma drug scores have been recognized as a risk factors for surgical failure of trabeculotomy [25][26][27][28]. In a recent study conducted by Okuda et al, researchers examined the perioperative factors that affected the surgical success of ab-interno microhook trabeculotomy.…”
Section: Topical Glaucoma Medicationsmentioning
confidence: 99%
“…In a recent study conducted by Okuda et al, researchers examined the perioperative factors that affected the surgical success of ab-interno microhook trabeculotomy. The findings revealed that patients taking anti-glaucoma eye drop medications for more than 4.5 years had a lower success rate of cataract surgery and microinvasive trabeculectomy [25]. These findings may be attributed to the substances found within glaucoma eye drops, such as benzalkonium chloride (BAK), that can cause prolonged inflammation and damage to the drainage of the aqueous humor through Schlemm's canal.…”
Section: Topical Glaucoma Medicationsmentioning
confidence: 99%
See 1 more Smart Citation